China's Pension System : A Vision - Dorfman, Mark C. (Washington, DC: World Bank, 2013)
China is at a critical juncture in its economic transition. A comprehensive reform of its pension and social security systems is an essential element of a strategy aimed toward achieving a harmonious society and sustainable development. Among policy makers, a widely held view is that the approach to pension provision and reform efforts piloted over the last 10-15 years is insufficient to enable China's economy and population to realize its development objectives in the years ahead. This volume suggests a national pension system that no longer distinguishes along urban and rural locational or hukou lines yet takes account of the diverse nature of employment relations and capacity of individuals to make contributions. This volume is organized as follows: the main text outlines this vision, focusing on summarizing the key features of a proposed long-term pension system. It first examines key trends motivating the need for reform then outlines the proposed three-pillar design and the rationale behind the design choices. It then moves on to examine financing options. The text continues by discussing institutional reform issues, and the final section concludes. The six appendixes provide additional analytical detail supporting the findings in the main text. The pension system design can play an important role in supporting or constraining such economic and demographic transitions: 1) fragmentation and lack of portability of rights hinder labor market efficiency and contribute to coverage gaps; 2) multiple schemes for salaried workers, civil servants, and, in some areas, migrants similarly impact labor markets; 3) legacy costs that are largely financed through current pension contributions weaken incentives for compliance and accurate wage reporting; 4) very limited risk pooling and interurban resource transfers limit the insurance function of the urban pension system and create spatial disparities in old-age income protection; 5) low retirement ages affect incentives and benefits and undermine fiscal sustainability; and 6) relatively low returns on individual accounts result in replacement rates significantly less than anticipated while at the macro level, are likely to inhibit wider efforts to stimulate higher domestic consumption.